Anatomical variation of nose and paranasal sinuses among patients with chronic rhinosinusitis on computer tomography - Shah, Rajeev Kumar (Birat Journal of Health Sciences, 2022)
Introduction: Chronic rhinosinusitis is one of the commonest diseases of sinonasal cavity seen in Ear nose throat clinic. Although chronic rhinosinusitis is a clinical diagnosis, CT scan imaging studies helps in accessing the disease and gives a clear anatomy of sinonasal cavity. Chronic rhinosinusitis is a group of disorders that is characterized by inflammation of the mucosa of the nose and paranasal sinuses of at least 12 consecutive weeks duration. There are number of factors that play role in the development of rhinosinusitis, including both host and environmental factors. CRS is a more persistent problem that requires a specific treatment approach. Methodology: This is a prospective comparative study which was conducted in Department of otorhinolaryngology of Birat Medical College and Teaching Hospital from 1st August 2020-31st Dec 2020. This study was approved by Institutional Review Committee of Birat Medical College and Teaching Hospital. 124 patients were taken in the study. The primary objective of the study was to determine the anatomical variation of nose and paranasal sinuses among patients with chronic rhinosinusitis on computer tomography. Informed and written consent was taken from all the subjects participating in the study. Result: A total of 124 patients was included in the study. Out of which 68 (54.76%) were men and 56 (45.24%) were female. The age of patients with CRS ranged from 15-75 years. Highest number of patients with CRS was in the range of 35- 44 years. Mucosal thickening was more common in maxillary sinus (91.12%) followed by ethmoidal (67.74%), spheniod (55.64%) and frontal (54.03%). Conclusion: CT scan is the most common tool to know the anatomical variations of the nose and para nasal sinuses. Moreover it is highly recommended for the patients suffering from chronic rhinosinusitis. CT scan provides all the sinonasal variations and then it becomes easier for the treating physician for better surgical planning and overall management of chronic rhinosinusitis.